Tinjauan Yuridis Penegakan Hukum Militer Terhadap Prajurit Militer Yang Melakukan Tindak Pidana Penyalahgunaan Narkotika (Studi Kasus Putusan Pengadilan Militer Bandung Nomor 41-K/PM. II-09/AD/III/2023) - Siregar, Rumagam Amputua Hasian (Jurnal Ilmiah Wahana Pendidikan, 2025)
This legal research aims to determine law enforcement against military soldiers, namely the Indonesian National Army or commonly referred to as the TNI, which in this study was involved in the criminal act of narcotics abuse and to determine the legal consideration by the panel of judges against military soldiers who commit criminal acts of narcotics abuse in the case of the Bandung Military Court decision Number 41-K/Pm. II-09/AD/III/2023. One of the threats of non-military countries is the abuse of narcotics because narcotics can destroy the nation's generation by damaging the nerves of the user's brain. Narcotics abuse in Indonesia is very worrying because it has reached various levels of society including State defense equipment, namely the Indonesian National Army. In essence, TNI soldiers are institutions that have a soldier's oath to be subject to applicable legal provisions and uphold the principles of discipline. But there are still unscrupulous TNI soldiers who violate the oath and commit criminal acts. One of the most common crimes committed by TNI soldiers is the abuse of narcotics. This legal research uses normative juridical research methods and conducts an analysis of court decisions. The data sources used in this study used primary and secondary legal materials, namely legislation, judges ' decisions, law books and law journals. In this study the defendant was tried in the Bandung Military Court and subject to a principal crime for 1 (one) year in prison and an additional crime that is dismissal from military service.